2006
DOI: 10.1208/pt070109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of residual water on antacid properties of sucralfate gel dried by microwaves

Abstract: The aim of this work was to study the acid neutralization characteristics of microwave-dried sucralfate gel in relation to the water content and physical structure of the substance. Several dried sucralfate gels were compared with humid sucralfate gel and sucralfate nongel powder in terms of neutralization rate and buffering capacity. Humid sucralfate gel and microwave-dried gel exhibited antacid effectiveness. In particular, the neutralization rate of dried gel powders was inversely related to the water conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The images were taken at the same magnification. A scanned area of the SEM image, a box of 200 μm width and 200 μm length, was analyzed by Image J software using the algorithm known as the “box counting method.”34,35 The analysis was carried out on five different area sections for each bead image considered and a mean fractal descriptor was obtained. The analysis was repeated on at least 10 beads for each batch.…”
Section: Methodsmentioning
confidence: 99%
“…The images were taken at the same magnification. A scanned area of the SEM image, a box of 200 μm width and 200 μm length, was analyzed by Image J software using the algorithm known as the “box counting method.”34,35 The analysis was carried out on five different area sections for each bead image considered and a mean fractal descriptor was obtained. The analysis was repeated on at least 10 beads for each batch.…”
Section: Methodsmentioning
confidence: 99%
“…25 It has been reported that the presence of water can slow down the acidneutralizing capacity of sucralfate. 12 27 Al MAS spectra clearly revealed different Al environments in the two forms (Figure 2a,b). Interestingly, unlike Form II, complete Al release does not occur in Form I.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The acid neutralization behavior of sucralfate gel in relation to the water content and physical structure was evaluated by Gainotti et al On comparing the neutralization rate of different dried sucralfate gels with humid gel and sucralfate non gel powder, it was found that the dried product shows a higher acid neutralization rate since its surface is in direct contact with the acid. 12 Sugar-free sucralfate chewable tablets were successfully formulated by Rajesh et al, and its acid neutralizing capacity was measured by NaOH titration. 13 There is no consensus in the literature about the acid neutralization behavior of sucralfate, where sucralfate interacts with acid and releases sucrose octasulfate and aluminum ions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several benefits can be obtained from technologies such as short processing time, better products uniformity and yields, energy saving, reduced production costs, as well as the ability to confer unique structural characteristics to the end materials. Recently, MW heating technology has been shown to be useful in the design of single-unit dosage forms such as solid dispersion, granules, and tablets [75][76][77][78]. Moreover, in the case of dextran-based formulations (i.e., alginate, pectin, and chitosan), MW irradiation leads to obtain xerogels with modified drug release properties due to the extent of polymer cross-linking and drug-excipient complexation [79,80].…”
Section: Prilling In Tandem With Microwave-assisted Dryingmentioning
confidence: 99%